Secure E-Voting With Blind Signature - Ibrahim, Subariah; Kamat, Maznah; Salleh, Mazleena; Abdul Aziz, Shah Rizan (2003)
With a rapid growth in computer networks, many people can access the network through the Internet and therefore an electronic voting can be a viable alternative for conducting an election. Electronic voting system must attempt to achieve at least the same level of security as ordinary elections. We have developed an electronic voting system, E-Voting for a general election. E-Voting system employs cryptographic techniques to overcome the security issues in the election process. In this system, voter’s privacy is guaranteed by using a blind signature for confidentiality and voter’s digital signature for voter’s authentication. E-Voting is implemented by employing Java socket technology and BouncyCastle cryptography provider. The provider, which is an open source library, is used to provide the secure communication channel. The voter’s private key for digital signature is protected by using password-based encryption with SHA and Twofish-CBC algorithm so that only valid voter can use it.